2022
DOI: 10.1097/rct.0000000000001354
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Liver and Pancreas Density With Chest Computed Tomography Score Progression and Laboratory Findings in Patients With COVID-19

Abstract: Objective: Abdominal involvement of COVID-19 is a current issue. We aimed to evaluate hepatic and pancreatic density alterations on computed tomography (CT) and to analyze whether these alterations had a relationship with chest CT score and laboratory findings.Methods: Patients with reverse transcription-polymerase chain reactionconfirmed COVID-19 from March 11, 2020, to February 6, 2021, were retrospectively analyzed. Patients were divided into nonprogressive and progressive groups according to their chest CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
(165 reference statements)
0
3
0
Order By: Relevance
“…Of note, lower values of liver CT attenuation and liver-to-spleen attenuation ratio were shown to correlate with the severity of COVID-19. Simultaneously, the presence of liver steatosis might concern up to 11% of cases, increasing the risk of hepatic injury [159,160]. Even though the findings of abdominal ultrasound examination are usually irrelevant in patients with normal results of liver function tests, in the case of significant increase in aminotransferases, vascular disorders and cholestatic abnormalities can be observed and related to a higher rate of mortality [161,162].…”
Section: Hepatic Imaging Findings In Covid-19 Patientsmentioning
confidence: 99%
“…Of note, lower values of liver CT attenuation and liver-to-spleen attenuation ratio were shown to correlate with the severity of COVID-19. Simultaneously, the presence of liver steatosis might concern up to 11% of cases, increasing the risk of hepatic injury [159,160]. Even though the findings of abdominal ultrasound examination are usually irrelevant in patients with normal results of liver function tests, in the case of significant increase in aminotransferases, vascular disorders and cholestatic abnormalities can be observed and related to a higher rate of mortality [161,162].…”
Section: Hepatic Imaging Findings In Covid-19 Patientsmentioning
confidence: 99%
“…On abdominal computed tomography (CT) scans of COVID-19 patients, hepatic hypodensity and fat stranding around the gallbladder were observed[ 78 ]. Some findings, such as a decrease in liver-to-spleen attenuation ratio and liver CT attenuation, may be relevant to the severity of the disease[ 79 , 80 ]. Chen et al [ 72 ] demonstrated that hepatic steatosis on CT scan was observed in 11.3% of COVID-19 cases, which enhanced the risk of hepatic dysfunction.…”
Section: Radiologic Findings Of the Liver In Covid-19 Patientsmentioning
confidence: 99%
“…US findings can be confirmed on abdominal CT. According to Lei et al [ 35 ], the most common CT abnormalities in COVID-19 patients include diffuse hypoattenuation of the liver (26%) – more common in severe patients (59%) – and the CT-quantified liver/spleen attenuation that can predict prognosis in COVID-19 patients[ 35 , 36 ]. Furthermore, because the liver is partially included in every chest CT, liver data from chest CT scans performed in many COVID-19 patients can be easily retrieved.…”
Section: Liver Disease Involvementmentioning
confidence: 99%